Exploring the Influence of the Evidence-Based Reasoning Model in the Inquiry Approach to Enhancing Students' Scientific Reasoning - Maghfiroh, Lailatul; Shofiyah, Noly (UIN Fatmawati Sukarno Bengkulu, 2023)
Scientific reasoning becomes a prerequisite skill for studying science. The fact is that this ability, especially at the junior high school level, is relatively low. One learning model that can be applied to overcome this problem is inquiry-based, evidence-based reasoning. This type of research is a one-group pretest-posttest design with a sample of 102 students taken by the purposive sampling technique. The research instrument was a two-tier multiple-choice test based on scientific reasoning indicators. The results of the study were analyzed using the N-gain test, and a value of 0.6 was obtained, or it could be concluded that there was an increase in students' scientific reasoning in the moderate category. An ANOVA test was also carried out, and a significance value of 0.258 > 0.05 was obtained, which indicated that there was no significant difference between groups or that the EBR model had a consistent impact on increasing students' scientific reasoning. Each indicator of scientific reasoning also experienced an increase in the moderate category. The existence of this research can be of particular concern to educators as they continue to train scientific reasoning abilities in various natural science materials so that a scientific mindset is formed in students.